麻疯树籽仁/壳乙醇提取物的体外抗氧化活性In vitro antioxidant activity of ethanol extracts of Jatropha curcas seed kernel and shell - 王钰，周一萍，汤运嘉，余莉莉，牛丽亚WANG Yu, ZHOU Yiping, TANG Yunjia, YU Lili, NIU Liya (Zhongguo youzhi, 2022)
为了提高麻疯树种子的开发利用价值，采用体外抗氧化实验对麻疯树籽仁/壳乙醇提取物抗氧化活性进行了研究。分别以麻疯树种子中的籽仁和籽壳为原料，经75%乙醇提取，在对提取物主要成分进行分析的基础上，以VE为阳性对照，测定两种提取物对自由基（DPPH自由基、ABTS+自由基、羟自由基和超氧自由基）的清除能力、还原能力以及抑制亚油酸自氧化能力。结果表明：麻疯树籽仁/壳乙醇提取物中多糖类物质总含量分别为47.67%和52.21%，酮类物质总含量分别为0.774%和 4.22%，麻疯树籽壳乙醇提取物中还含有0.30%的多酚类物质；麻疯树籽仁/壳乙醇提取物均具有一定的抗氧化活性，其中籽壳乙醇提取物对DPPH自由基、ABTS+自由基、羟自由基、超氧自由基的清除效果较好；麻疯树籽仁/壳乙醇提取物的还原能力和对亚油酸自氧化的抑制能力相对较弱。麻疯树籽壳乙醇提取物的抗氧化活性优于籽仁乙醇提取物，可能与籽壳乙醇提取物中含有较多的黄酮类和多酚类物质有关。 In order to improve the exploitation value of Jatropha curcas seed, the antioxidant activities of ethanol extracts of Jatropha curcas seed kernel and shell were investigated using in vitro antioxidant assays.The kernel and shell of Jatropha curcas seed were extracted by 75% ethanol respectively, and based on the analysis of the main components of the extracts, vitamin E was used as positive control, the scavenging ability on free radical (DPPH radical, ABTS+ radical, hydroxyl radical and superoxide radical ), reducing power and inhibition ability for linoleic acid autoxidation of the two extracts were determined.The results showed that the total content of polysaccharides in the ethanol extract of Jatropha curcas seed kernel/shell was 47.67% and 52.21%, and the total content of ketones was 0.774% and 4.22%, respectively. The ethanol extract of Jatropha curcas seed shell also contained 0.30% polyphenols. The two extracts had certain antioxidant activity, and the extract of seed shell was more effective in scavenging DPPH radical, ABTS+ radical, hydroxyl radical and superoxide radical than that of the extract of seed kernel. The reducing ability and inhibitory ability of linoleic acid autoxidation of the two extracts were relatively weak. The antioxidant activity of the ethanol extract of Jatropha curcas seed shell was better than that of the ethanol extract of Jatropha curcas seed kernel, which may be related to the rich content of flavonoids and polyphenols in the ethanol extract of shell.